Do ownership structure and corporate governance mechanisms affect dividend payouts? Evidence from Indonesia - Kusumaningtyas, Qinthara (Ifma Publishing, 2022)
This research aims to show how ownership structure and corporate governance mechanisms influence the dividend policies of nonfinancial companies listed on the Kompas 100 index from 2015–2018. The independent variables are foreign ownership, insider ownership, board independence, board intensity, and board size; the dependent variables are dividend policy measured with dividend payout ratio (DPR), dividend yield (DY), and dividends to total assets (DTA). Six control variables were also considered: leverage, volatility (risk), asset tangibility, age, sales growth, and profitability based on annual data and reports from non-financial registered companies listed on the Kompas 100 Period Stocks Index from 2015–2018 (180 observations). Purposive sampling with balanced panel data was used. The model used in this research is a data panel with a fixed-effect model; random effect model approaches were also utilized. The results show that foreign ownership, insider ownership, board independence, board intensity, and board size do not significantly affect dividend policy, except board intensity significantly affects dividend payout ratio.